Growth of Gracilaria under Different Planting Distances in Pond - Sunarto, . (Indonesian Society of Scientific Aquaculture (ISSA), 2009)
The use of non-productive shrimp ponds for cultivation of Gracilaria is one of the strategies that can be performed to achieve production target of seaweed. This study was conducted to determine the influence of different planting distances on growth of Gracilaria cultivated in pond. Gracilaria was separately planted in distant of 20x20 cm; 25x25 cm; 30x30 cm and 35x35 cm in pond for 45 days cultivation. Relative growth rate and thallus length increment were measured to obtain an optimal planting distance. The results of study showed that 25x25 cm planting distance resulted in a higher relative growth rate (137.8%) and increment of thallus length (15.3%) compared with other treatments. Thus, cultivation of Gracilaria in an unproductive pond with 25x25 cm planting distance may improve production. Keywords : non-productive ponds, planting distance, Gracilaria ABSTRAK Pemanfaatan tambak udang yang tidak produktif untuk budidaya Gracilaria merupakan salah satu strategi yang dapat dilakukan untuk mencapai target produksi rumpul laut. Penelitian ini dilakukan untuk mengetahui pengaruh jarak tanam yang berbeda terhadap pertumbuhan Gracilaria di tambak. Gracilaria ditanam terpisah dengan jarak 20x20 cm; 25x25 cm; 30x30 cm dan 35x35 cm di tambak selama 45 hari pemeliharaan. Pertumbuhan relatif dan panjang thalus diukur untuk memperoleh jarak tanam yang optimal. Hasil penelitian menunjukkan bahwa jarak tanam 25x25 cm memberikan pertumbuhan relatif (137.8%) dan pertambahan panjang thalus (15.3%) tertinggi dibandingkan dengan perlakuan lainnya. Dengan demikian, budidaya Gracilaria di tambak tidak produktif dengan jarak tanam 25x25 xm diduga sangat membantu untuk mencapai target produksi rumput laut. Kata kunci : tambak non-produktif, jarak tanam, Gracilaria